2008
DOI: 10.1063/1.2891083
|View full text |Cite
|
Sign up to set email alerts
|

Influence of surface ligands on saturation magnetization of FePt nanoparticles

Abstract: The influence of organic ligands on the saturation magnetization (MS) of chemically disordered face-centered-cubic (fcc) FePt nanoparticles (NPs) was investigated. By increasing the basicity and/or surface coverage of ligands, the MS of fcc-phase FePt NPs decreases due to an increase in electron donation from the ligand to the Fe d bands. FePt NPs capped with 1-octanethiol or 1-dodecanethiol show larger MS than as-synthesized NPs capped with oleic acid due to a thinning of the nonmagnetic shell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 9 publications
0
37
1
Order By: Relevance
“…Magnetism at the particle's surface is governed by a breaking of the lattice symmetry; which induces changes in the topology of the surface magnetic moments and consequently in the exchange integrals (through a change of superexchange angles and/or distances between moments), thus leading to an increase of anisotropy (i.e., a surface component) and a decrease in saturation magnetization [4,5]. Moreover, several authors have shown that the interaction between polymer molecules and surface atoms can induce modifications in the NPs magnetic properties [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…Magnetism at the particle's surface is governed by a breaking of the lattice symmetry; which induces changes in the topology of the surface magnetic moments and consequently in the exchange integrals (through a change of superexchange angles and/or distances between moments), thus leading to an increase of anisotropy (i.e., a surface component) and a decrease in saturation magnetization [4,5]. Moreover, several authors have shown that the interaction between polymer molecules and surface atoms can induce modifications in the NPs magnetic properties [6,7].…”
Section: Introductionmentioning
confidence: 98%
“…This strategy is also applicable to FePt NPs, because the Pt-thiol bond is much stronger than the Pt-amine bond. Additionally, we recently found that FePt NPs capped with 1-octanethiol or 1-dodecanethiol show larger saturation magnetization than assynthesized NPs capped with oleic acid owing to a thinning of the nonmagnetic shell [8]. The saturation magnetization of FePt NPs decreases owing to an increase in electron donation from the ligand to the Fe d bands.…”
Section: Introductionmentioning
confidence: 98%
“…FePt in a bulk state has a larger uniaxial anisotropy than bulk-CoCr, which has basically been used in the present hard disk drive. In addition to FePt nanoparticles [21][22][23][24][25][26][27][28][29][30], other alloy nanoparticles with the fct structure (CoPt [31][32][33][34][35][36][37][38][39][40] and FePd [41][42][43][44]) have been prepared by chemical reduction methods as a candidate of the promising magnetic nanomaterials for a new magnetic device.…”
Section: Introductionmentioning
confidence: 99%